Rubberwood resource in Ghana and the perspective of its development - Addae-Mensah A G; Eastin I (Wood News, 1991)
Though the rubber plantations in Ghana constitute only 0.1 per cent of the rubber planted area in Asia and 2.5 per cent of the rubber planted area in West Africa, rubberwood has an important role to play as a raw material for the forest products industry and offers a relatively unexploited resource base for the country. This resource can be managed on a sustained yield basis and the production of latex rubber can be used to offset some or most of the costs of planting and management. Earnest efforts should be made by the country in terms of infrastructure development, raw material treatment, product manufacturing, technological development and marketing strategies in order to realise the potential supply of the rubberwood and to manufacture varieties of products out of it.
Keywords: Ghana; Rubberwood